Bioarchaeology of affluence: Gold plate dentures as conspicuous consumption in the 19th century US South - Phillips, Shawn (Journal of Bioarchaeological Research, 2024)
The first examples of gold plate dentures recovered from an archaeological context are presented. The field of archaeology has a robust literature on the notion of “conspicuous consumption,” bioarchaeology, in contrast, has focused class-based research on differential measures of health, with an emphasis on poverty indicators rather than affluence. Recent bioarchaeological workers have suggested the mouth as a nexus for identity and class representation. This study presents gold plate dentures as a bioarchaeological artifact that reflects affluency and conspicuous consumption. Through the process of mastication, dentures interact directly with alveolar tissues and, simultaneously, serve purposes of functionality as well as markers of affluence and identity.